2023
DOI: 10.9758/cpn.2023.21.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine Treatment for Post-traumatic Stress Disorder: A Systematic Review of the Literature

Abstract: Paroxetine and Sertraline are the only medications approved in posttraumatic stress disorder (PTSD). However, about 60% of traumatized patients fail to show an adequate clinical response. Second generation antipsychotics are recommended as second-line monotherapy or third-line augmentation strategies and quetiapine appears as one of the most used and promising agents. Up to date, no reviews assessed the efficacy of quetiapine in the treatment of PTSD. We aimed to assess the effectiveness and general safety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Quetiapine and olanzapine were also included in the DrugBank in association with PTSD. Research shows that treatment with quetiapine, which is commonly used to treat bipolar disorder, schizophrenia, and major depressive disorder, can improve the following PTSD symptoms: re-experiencing, avoidance, hyperarousal, flashbacks, depressive symptoms, anxiety, psychotic symptoms, insomnia, and nightmares ( Crapanzano et al, 2023 ). Furthermore, olanzapine, commonly used to manage schizophrenia, bipolar 1 disorder, and agitation associated with these conditions, has been shown to alleviate anxiety- and memory-related behavioral symptoms caused by PTSD in rat models ( Reddy and Krishnamurthy, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quetiapine and olanzapine were also included in the DrugBank in association with PTSD. Research shows that treatment with quetiapine, which is commonly used to treat bipolar disorder, schizophrenia, and major depressive disorder, can improve the following PTSD symptoms: re-experiencing, avoidance, hyperarousal, flashbacks, depressive symptoms, anxiety, psychotic symptoms, insomnia, and nightmares ( Crapanzano et al, 2023 ). Furthermore, olanzapine, commonly used to manage schizophrenia, bipolar 1 disorder, and agitation associated with these conditions, has been shown to alleviate anxiety- and memory-related behavioral symptoms caused by PTSD in rat models ( Reddy and Krishnamurthy, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, AAPs are being used more often in recent years to treat anxiety, MDD, PTSD and other disorders. Quetiapine (QTP), a second-generation AAP commonly prescribed for the treatment of schizophrenia (Dev & Raniwalla, 2000;Small et al, 1997) and acute bipolar mania (Janicak & Rado, 2012), is now also used to treat insomnia (Lin et al, 2023), MDD (Ravindran et al, 2022), anxiety (Bandelow et al, 2010;Crapanzano et al, 2021;Ravindran et al, 2022), and PTSD (Crapanzano et al, 2023). Like other AAPs, QTP is structurally similar to clozapine and acts as an antagonist to serotonin, dopamine, histamine, and adrenergic receptors (Burns, 2001;Saller & Salama, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Quetiapine fumarate (Seroquel®) (QTP) is a second-generation atypical antipsychotic drug that has been commonly prescribed for the treatment of schizophrenia (Dev & Raniwalla, 2000;Small, Hirsch, Arvanitis, Miller, & Link, 1997), acute bipolar mania (Janicak & Rado, 2012), insomnia (Lin, Chiang, Tseng, Tam, & Loh, 2023), major depressive disorder (depression) (Ravindran et al, 2022), anxiety (Bandelow et al, 2010;Crapanzano, Damiani, & Guiot, 2021;Ravindran et al, 2022), Post-traumatic stress disorder (Crapanzano, Damiani, Casolaro, & Amendola, 2023) and other psychological disorders (Saller & Salama, 1993). Like other atypical antipsychotics, QTP is structurally similar to clozapine and acts as an antagonist to serotonin, dopamine, histamine, and adrenergic receptors (Burns, 2001;Saller & Salama, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in China explored the off-label use of antipsychotic medications in psychiatric patients, excluding those with schizophrenia spectrum disorder or bipolar disorder [3]. The findings revealed that antipsychotics were utilized across a broad range of psychiatric conditions, with the highest usage observed in patients with dissociative and/or conversion disorders, as well as other mental disorders, including somatoform disorders, major depressive disorder, anxiety disorder, and insomnia [5].…”
Section: Introductionmentioning
confidence: 99%